DETECTION OF CO-INFECTION IN DISEASED GUPPY (POECILIA RETICULATA): TETRAHYMENA SP., MYXOBOLUS SP. AND OPPORTUNISTIC BACTERIA - Cigdem Urku; Mustafa Kemal Meydan (Archives of Veterinary Medicine)
The guppy (Poecilia reticulata) is one of the world's most popular freshwater aquarium fish. The present study aims to determine the cause of mortality in guppies obtained from the ornamental fish farm in Istanbul province and to detect tissue damage. Externally diseased guppies showed sloughing scales and large ulcerative skin lesions on the body surface. Bacteriological inoculation from internal organs was made onto Tryptic Soy Agar (TSA). After incubation, isolated bacteria were identified as Aeromonas hydrophila and Vibrio parahaemolyticus according to their physiological, morphological, and API 20E profile. As a result of the parasitological examination, Tetrahymena sp. and Myxobolus sp. were found on the skin and intestinal lumen of the diseased guppy, respectively. Histopathologically, cytoplasmic vacuolation in the liver, degeneration, and necrosis of the tubular epithelium and granuloma-like structure in the kidney, vacuolization of epithelial cells in the intestinal lumen, hyperplasia of the gill and Tetrahymena sp. between necrotic muscles were observed. Interestingly, Myxobolus sp. spores were only detected in the intestinal lumen. Co-infection of guppies was determined to cause severe disease with high mortality and tissue damage. The synergistic effects of pathogens may cause more damage to diseased guppies. This report is the first detailed report containing new histopathological findings of tetrahymeniosis and the first detection of Myxobolus sp. in the gut of diseased guppy in Turkey.